PELESTARIAN HUTAN RAKYAT KAITAN DENGAN KEARIFAN LOKAL DI DESA TANAH TOWA KECAMATAN KAJANG KABUPATEN BULUKUMBA - Kaharudin; Jelly Robot; Erick Lobja (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2020)
The problem in this research is to determine the forms of local wisdom in preserving community forests in Tanah Towa Village, Kajang District, Bulukumba Regency, South Sulawesi Province. This study aims to examine forms of local wisdom in Tanah Towa Village in the preservation of community forests. The research method used is descriptive qualitative. The data collection techniques in this study were carried out through observation, interviews, and documentation. The results of the study showed that the preservation of community forests was carried out. The people of Tanah Towa Village are still well managed and the existence of community forests greatly supports land conservation and maintains the availability of clean water in the village and improves the economy of the village community. The conclusion of this study is that there is a very close relationship between forest preservation and local wisdom in Tanah Towa Village so that there are 6 forms of local wisdom related to forest preservation, among others, traditional institutions in forest preservation, belief in patuntung kamase-mase simple), install ri kajang (rules), prohibition of cutting down trees, prohibition of killing and taking animals, and traditional rituals. And among the local wisdoms, there isasang Ri Kajang (rule) which has a role in managing all the activities of the Tanah Towa village community.